Cytotoxic Tobacco Smoke in The Cornea of Wistar Rats Fed Turmeric (Curcuma Domestica Val.) Extract - Agapietta Kusumawardani; Kurniati Sarwendah; Laelatul Rahmad; Nida Ul Milah; Novi Herliyani; Bambang Sutrisno; Hastari Wuryastuty; R Wasito (Jurnal Sain Veteriner, 2013)
Abstract An increasing number of smokers who tend to rise rapidly from year to year has become a major focus of public health issues. Exposure to environmental tobacco smoke, containing toxic chemicals can trigger acute or chronic inflammation and oxidative stress in the eyes. To overcome this condition, phytotherapeutic and/or phytopreventive approaches which are efficatious, safe and cheap is needed. One of spices from Indonesia which is greatly possible to be promoted as a herbal medicine, is a phytochemical curcumin in turmeric. This present study was conducted to identify and determine the effects of turmeric extract (Curcuma domestica Val.) as phytotherapeutic and/or phytopreventive in the eyes lesion of Wistar rats induced by cigarette smokes. Twenty male Wistar rats at 3 months old were divided randomly into four groups of five each. Those were the control group (KI), the group given 9 cigarettes smoke/day (K II), the group given turmeric extract 1 ml 0, 25% /day (K III) and the group given 9 cigarettes smoke/day and 0, 25% turmeric extract 1 ml /day (K IV) for 60 days. Water and feed was given ad libitum. At the end of the experiment, all rats were euthanized with ether, necropsied andeyes balls were collected, fixed formalin 10% and stained with routine hematoxylin-eosin. The results of the present study indicated that 9 cigarettes smoke/day increased mitotic activity and caused hyperplasia in the corneal epithelial cells (K II), and addition of turmeric extract 0, 25% 1 ml per oral for 60 days prevented both mitotic activity and hyperplasia in the corneal epithelial cells (K IV). Extract of turmeric (Curcuma domestica Val.) has been proved to have herbal therapeutic and/or preventive effects againts the pathotoxicological cigarette smokes. Further study needs to be done to more evaluate pathogenesis of the eyes lesions and phytotherapeutic and/or phytopreventive effects of turmeric extract as well.